2022
DOI: 10.3389/fimmu.2022.910337
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Clinical and Laboratory Characteristics of Ocular Syphilis: 6-Years Case Series Study From an Eye Center in East-China

Abstract: PurposeTo report the demographic, clinical, and laboratory characteristics of ocular syphilis based on a 6-year case series study from an eye center in East-China.MethodsA total of 131 cases (191 eyes) of ocular syphilis and the annual number of total syphilis cases from January 2016 to December 2021, were included in this study. Detailed medical records including systemic and ophthalmic medical history, a complete ophthalmic examination, color fundus photography, B-type ultrasound, fundus fluorescein angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…While ocular involvement is rare in syphilis, 7 all of the study patients were diagnosed with the ocular involvement. Delay in diagnosis and improper treatment can lead to irreversible visual loss.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While ocular involvement is rare in syphilis, 7 all of the study patients were diagnosed with the ocular involvement. Delay in diagnosis and improper treatment can lead to irreversible visual loss.…”
Section: Discussionmentioning
confidence: 97%
“…14 We believe that our case series will increase awareness among the clinicians about the OS as the delay in diagnosis and improper treatment can lead to irreversible visual loss. 7,15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 and the calculation of Goldman-Whitmer coefficient (GWC) also provided a basis for the diagnosis of ocular syphilis. Aqueous humor GWC is also a diagnostic criteria for ocular syphilis ( 5 ). GWC ≥4 indicates that the amount of Treponema -specific antibodies in the aqueous humor significantly exceeds circulating Treponema- specific antibodies, which in consideration of the blood-eye barrier suggests the antibody is produced in situ by ocular tissues ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ocular syphilis in the United Kingdom was 0.3 cases per 1,000,000 people, and 0.6% of syphilis patients had ocular symptoms ( 4 ). A 6 year case study in eastern China demonstrated that ocular syphilis was comorbid in 5.1% of total syphilis cases ( 5 ). In Shanghai, 213 (2.6%) of 8,310 syphilitic patients had ocular manifestations from October 2009 to October 2017 ( 6 ).…”
Section: Introductionmentioning
confidence: 99%